The RNA binding site of bacteriophage MS2 coat protein. - Peabody, D S (1993)
The coat protein of the RNA bacteriophage MS2 binds a specific stem-loop structure in viral RNA to accomplish encapsidation of the genome and translational repression of replicase synthesis. In order to identify the structural components of coat protein required for its RNA binding function, a series of repressor-defective mutants has been isolated. To ensure that the repressor defects were due to substitution of binding site residues, the mutant coat proteins were screened for retention of the ability to form virus-like particles. Since virus assembly presumably requires native structure, this approach eliminated mutants whose repressor defects were secondary consequences of protein folding or stability defects. Each of the variant coat proteins was purified and its ability to bind operator RNA in vitro was measured. DNA sequence analysis identified the nucleotide and amino acid substitutions responsible for reduced RNA binding affinity. Localization of the substituted sites in the three-dimensional structure of coat protein reveals that amino acid residues on three adjacent strands of the coat protein beta-sheet are required for translational repression and RNA binding. The sidechains of the affected residues form a contiguous patch on the interior surface of the viral coat.